Using Project Performance to Measure Effectiveness of Quality Management System Maintenance and Practices in Construction Industry - Tiong Kung Leong; Norhayati Zakuan; Muhamad Zameri Mat Saman; Mohd. Shoki Md. Ariff; Choy Soon Tan (The Scientific World Journal)
This paper proposed seven existing and new performance indicators to measure the effectiveness of quality management system (QMS) maintenance and practices in construction industry. This research is carried out with a questionnaire based on QMS variables which are extracted from literature review and project performance indicators which are established from project management's theory. Data collected was analyzed using correlation and regression analysis. The findings indicate that client satisfaction and time variance have positive and significant relationship with QMS while other project performance indicators do not show significant results. Further studies can use the same project performance indicators to study the effectiveness of QMS in different sampling area to improve the generalizability of the findings.